Self-motion evokes precise spike timing in the primate vestibular system - Mohsen Jamali (Nature Portfolio, 2016)
Early vestibular pathways are thought to code sensory inputs regarding self-motion via changes in firing rate. Here, the authors record from both regular and irregular afferents in macaques, and find both irregular afferents and central neurons also represent self-motion via temporally precise spike timing.